2018
DOI: 10.1080/14681811.2018.1535969
|View full text |Cite
|
Sign up to set email alerts
|

South African contributions to LGBTI education issues

Abstract: South Africa stands out in the African region for its protection of lesbian, gay, bisexual, transgender and intersex (LGBTI) rights. This article examines South Africa's contributions to local policy for LGBTIs and to work on LGBTI issues in education policy and education rights progress internationally. It also considers broader South African contributions to the theorisation of gender and sexuality. Data derive from an analysis of 102 interviews with key informants participating in high-level global networki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…We must also mention the South Africa Contributions to LGTBI education issues as pointed Jones (2018) as well as some researchers who have described the extreme effects of what we call harmfull sexual violence and bullying that have come to promote suicide -although it is not a key objective of this paper-on occasions outside and within educational centers ( González Contreras et al, 2020 ; Pérez-Jorge et al., 2020 , Pérez-Jorge et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…We must also mention the South Africa Contributions to LGTBI education issues as pointed Jones (2018) as well as some researchers who have described the extreme effects of what we call harmfull sexual violence and bullying that have come to promote suicide -although it is not a key objective of this paper-on occasions outside and within educational centers ( González Contreras et al, 2020 ; Pérez-Jorge et al., 2020 , Pérez-Jorge et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…For examples, the USA and South Africa have legalized same sex act since 2003 and 2006 respectively, and both countries have made tremendous progress in improving MSM and TGW equalities. Yet they continue to still face hostility, stigma and discrimination (26,27,28,29). In many African countries, Rwanda included, the strong culture and religion beliefs do not necessarily promote tolerance to people of different sexual identities or orientation, having a law will not likely translate into immediate changes on how MSM and TGW are perceived by the society.…”
Section: Discussionmentioning
confidence: 99%
“…Without policy, other crime prevention activities could not be sustainable. Jones (2019) studying South African contributions to LGBTI education issues had revealed that proper education is an effective mechanism in reduction of crimes. It makes people to understand the crime situation of their areas, kind of crimes, mode of operation and possible culprits.…”
Section: Literature Reviewmentioning
confidence: 99%